2019
DOI: 10.1519/jpt.0000000000000157
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Walking Speed in Subjective and Mild Cognitive Impairment: A Cross-Sectional Study

Abstract: Usual walking speed is reduced in a graded fashion with the early symptoms of cognitive impairment. Our results suggest that reduced walking speed at both usual and fast speed is associated with impaired cognitive function, and that walking speed could be affected at very early stages of neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 43 publications
3
42
1
1
Order By: Relevance
“…This is one of the first studies in the literature to assess the longitudinal relationship between slow gait speed and cognitive function in those with a diagnosis of AD At baseline, the only significant predictors of slow gait speed were greater age and poorer cognition in multivariate analysis. This finding is noteworthy and is largely consistent with previous studies in the literature which have demonstrated a relationship between cognitive function and gait speed in a cross-sectional manner in those with AD [17][18][19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is one of the first studies in the literature to assess the longitudinal relationship between slow gait speed and cognitive function in those with a diagnosis of AD At baseline, the only significant predictors of slow gait speed were greater age and poorer cognition in multivariate analysis. This finding is noteworthy and is largely consistent with previous studies in the literature which have demonstrated a relationship between cognitive function and gait speed in a cross-sectional manner in those with AD [17][18][19].…”
Section: Discussionsupporting
confidence: 92%
“…Whilst the evidence for the relationship between slow gait speed and later dementia risk is mounting, the relationship between gait speed and cognitive trajectories in those with Alzheimer Disease (AD) is less clear. Whilst a handful of studies have evaluated the association between gait speed and dementia in cross-section [17][18][19], longitudinal analyses are limited. A notable study has demonstrated a decline in gait speed associated with clinical progression in those with Mild Cognitive Impairment (MCI) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies found an association between changes in gait and EF, 12,46 however, the divergent results of the present investigation may have occurred because the authors used instruments to assess EF and gait variables different from those used in this study investigation. The literature shows that in addition to the consistency in the results and quality of the studies, there seems to be variations in the results according to the instrument chosen for the evaluation, sample size, population studied, and the evolution of cognitive impairment in the volunteers.…”
Section: Discussioncontrasting
confidence: 58%
“…The literature shows that in addition to the consistency in the results and quality of the studies, there seems to be variations in the results according to the instrument chosen for the evaluation, sample size, population studied, and the evolution of cognitive impairment in the volunteers. 12,22,46,47 As MCI and dementia become more prevalent with the increase in age, early diagnosis is essential. The results of the present study seem to indicate that slowing GS is a potential early marker of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Gait disturbance has also been found in neurodegenerative disease and aging, which may give insight into longer-term effects of multiple mTBIs. For example, the walking speed of patients with AD is slower than healthy older adults (Johansson et al, 2017) and walking speed differences appear already in those with mild cognitive impairment (MCI; Knapstad et al, 2019), suggesting that gait change is an early event and can be used to diagnose potential problems. It is therefore possible that long-term tracking of gait post-mTBI can reveal future risk for developing neurodegenerative conditions related to multiple mTBIs and may represent a sensitive dynamic balance measure for these cases.…”
Section: Current Assessment Tools For Mtbimentioning
confidence: 99%